Inhibitory Effects of Nigella sativa Seed Extract on Adrenaline-Induced Dyslipidemia and Left Ventricular Hypertrophy in Rats (Journal of Scientific Research, 2013)
The aim of this study was to investigate the inhibitory effect of Nigella sativa seed extract (abbreviated as NSSE) on adrenaline-induced dyslipidemia and left ventricular hypertrophy (LVH) in rats. Intraperitoneal injection of adrenaline for two weeks induced dyslipidemia whereas injection of adrenaline for four weeks induced both dyslipidemia and LVH significantly, compared with normal rats. Injection of NSSE with different doses (0.5, 1 and 1.5 mg/kg body weight, BW) on adrenaline-induced dyslipidemic rats (AIDRs) for two weeks significantly reduced TC, TG and LDL-C and increased HDL-C compared with AIDRs and the most effective dose was 1.5 mg/kg BW. Treatment with NSSE (1.5 mg/kg BW) on AIDRs for eight weeks, significant anti-dyslipidemic effect was observed. Moreover, NSSE significantly increased free radical scavenging activity and attenuated the LVH and cardiomyocyte size compared with AIDRs. The results suggested that the anti-dyslipidemic, antioxidative and inhibitory effects of NSSE on LVH were closely resembled to that of atorvastatin, a most effective lipid lowering agent. Therefore, NSSE might be used as a therapeutic alternative or as a combination with drug in the treatment of dyslipidemia and LVH.Keywords: Adrenaline; Dyslipidemia; LVH; NSSE; Atorvastatin.© 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i2.12203        J. Sci. Res. 5 (2), 325-334 (2013).